Soccer analytics: Unravelling the complexity of "the beautiful game" - Bornn, L.; Cervone, D.; Fernandez, J. (Significance, 2018)
While national soccer teams compete this June to win the World Cup, analysts will be crunching data behind the scenes to pursue an advantage. Luke Bornn, Dan Cervone and Javier Fernandez explore the evolution of soccer analytics.